Effectiveness of current digital cognitive behavioural therapy for insomnia interventions for adolescents with insomnia symptoms: A systematic review and meta‐analysis - Cleary, Melissa A.; Richardson, Cele; Ross, Ruby J.; Heussler, Helen S.; Wilson, Andrew; Downs, Jenny; Walsh, Jennifer (Journal of sleep research, 2025)
Summary Sleep problems occur in up to 20%–45% of adolescents. This systematic review and meta‐analysis examined the effectiveness of digital sleep interventions, based on cognitive behavioural therapy for insomnia, for adolescents with insomnia symptoms. The objective was to synthesise and quantify, through meta‐analyses, changes in sleep following completion of a digital sleep‐based intervention. MEDLINE, PubMed, PsycINFO, Scopus, EMBASE, CENTRAL, and Web of Science databases were searched from January 2012 to March 2024. Within‐subject studies or randomized–controlled trials reporting the effects of digital cognitive behavioural therapy for insomnia were included. Risk of bias was assessed using the integrated quality criteria for the review of multiple study designs. Random‐effects meta‐analyses estimated pooled standardised within‐subject mean differences to assess effectiveness. Nine studies involving 486 adolescents were included. Digital cognitive behavioural therapy for insomnia interventions were effective in reducing insomnia symptoms (Hedges’ g = 1.40), subjective sleep‐onset latency (Hedges’ g = 0.72) and waking after sleep onset (Hedges’ g = 0.47), and increasing subjective and objective total sleep time (Hedges’ g = −0.29 and −0.23, respectively). Other objective measures of sleep did not improve. All studies met the minimum ICROMS score and were considered to be of sufficient quality. Seven within‐subject studies failed to satisfy all mandatory criteria. These results suggest that digital cognitive behavioural therapy for insomnia interventions are effective in improving adolescent's perceptions of their sleep, but are less effective at improving some objective measures of sleep. To achieve a clear understanding of how digital cognitive behavioural therapy for insomnia interventions compare with other behavioural interventions, additional high‐quality randomized–controlled trials comparing digital cognitive behavioural therapy for insomnia interventions with traditional in‐person modalities are needed. (PROSPERO;CRD42021287479).